NON-POLAR FRACTINATION OF SUKARI DATE EXTRACT EFFECT ON LEUKOCYTES IMUNE RESPONSE OF MALE WISTAR INDUXED BY MELOXICAM - Anshar, Amelia Ramadhani; Fawziah, Dwiyuci; Nurdin, Muhammad Ardiansyah (Buletin Veteriner Udayana, 2022)
Meloxicam is a non-steroidal anti-inflammatory drug (NSAID) is often prescribed by veterinarian because it has anti-inflammatory effect. However, inappropriate consumed of meloxicam can cause serious effects on immune system. As a preventive action to increase immune system is to provide an immunostimulant. Dates are plants that contain active compounds that have an immunostimulant effect. This study aimed to determine the immunostimulant effect of Sukari Date Extract on male Wistar rats induced by toxic dose of meloxicam. The samples used in this study were 24 rats which were divided into 4 groups. The negative control group (K1) was the group that was given 1% NaCMC, the positive control group (K2) was the group that was given 1% NaCMC and meloxicam 30 mg/BW on the 11th day, treatment group 1 (P1) was the group that was given the extract. Sukari dates 500 mg/BW and meloxicam 30 mg/BW on the 11th day, and treatment group 2 (P2) were given 1000 mg/BW extract of Sukari dates and 30 mg/BW meloxicam on the 11th day. Blood sampling will be used to analyze total value of leukocytes and leukocyte differentiation was carried out on the 12th day. The test results showed that the dates extract at a dose of 500 mg/kg and 1000 mg/kg could improve and neutralize the toxic dose of meloxicam with values ??for total leukocytes 8.15 103/µL and 8.22 103/µL, for lymphocytes 66.83% and 72.50%. , neutrophils were 15.33% and 23.67%, monocytes were 17.33% and 3.50%, respectively. Meanwhile, eosinophils and basophils had no effect, with values ??for eosinophils of 0.50% and 0.33%, respectively, for basophils 0.00% and 0.00%. Date extract has a good immunostimulant effect on total leukocytes, lymphocytes, neutrophils and monocytes, but on eosinophils and basophils it does not have a significant effect.